HIV-1 drug-resistant mutations and related risk factors among HIV-1-positive individuals experiencing treatment failure in Hebei Province, China. Issue 1 (December 2017) - Lu, Xinli; Zhao, Hongru; Zhang, Yuqi; Wang, Wei; Zhao, Cuiying; Li, Yan; Ma, Lin; Cui, Ze; Chen, Suliang
Abstract Background To understand HIV-1 drug resistance in 11 prefectures of Hebei Province, China, we implemented a cross-sectional HIV-1 molecular epidemiological survey. Methods Blood samples were collected from 122 newly diagnosed drug-naïve HIV-1-positive individuals and 229 antiretroviral therapy (ART)-failure individuals from 11 prefectures in Hebei Province, China. Patient demographic data were obtained via face-to-face interviews using a standardized questionnaire when blood samples were collected. Genotyping of HIV-1 drug resistance (DR) was implemented using an in-house assay. Results In this study, the overall prevalence of HIV-1 DR was 35.5%. The prevalence of HIV-1 DR in participants experiencing treatment failure and ART-naïve participants was 51.9 and 5.9%, respectively. Mutations in protease inhibitors, nucleoside reverse transcriptase inhibitors (NRTIs), and non-NRTI (NNRTIs), as well as dual and multiple mutations were extensively seen in participants experiencing treatment failure. The proportions of NNRTI mutations (χ2  = 9.689, p  = 0.002) and dual mutations in NRTIs and NNRTIs (χ2  = 39.958, p  < 0.001) in participants experiencing treatment failure were significantly higher than those in ART-naïve participants. The distributions of M184V/I and M41L mutations differed significantly among three main HIV-1 genotypes identified. Viral load, symptoms in the past 3 months, CD4 counts, transmission route, and the duration of ART were found to be associated with HIV-1 DR. Conclusions Our results suggest that new prevention and control strategies should be formulated according to the epidemic characteristics of HIV-1-resistant strains in Hebei Province, where antiretroviral drugs are widely used.